THE USE OF LEMBAR KERJA SISWA AS A LEARNING MEDIUM AMONG INDONESIAN HIGH SCHOOL STUDENTS - Fitriana, Tiara Kusuma; Lestari, Ika Wahyuni (Journal of Foreign Language Teaching and Learning, 2019)
One of the learning media used by Indonesian high school students to support their learning is in the form of a student worksheet, commonly called Lembar Kerja Siswa (LKS). This study aims to examine the reasons why Indonesian high school students used LKS as their learning media and the challenges they faced in using LKS both during the teaching and learning process in the classroom and in their independent learning. This research was conducted at one public school in Yogyakarta, Indonesia. Four students who used LKS during their English lesson and in their autonomous learning were purposefully selected as the participants of the study. To obtain the data, one-on-one in-depth interviews were administered. The results of the study revealed that the reason for using LKS was to support their learning due to its content, usefulness, handiness, and affordable price. Nonetheless, the participants also found that LKS was challenging to use because of its short explanation, lack of questions, the ambiguity of answers, and poor face validity. At last, suggestions to improve the use of LKS as a learning medium were addressed.